OW_GERICHTE AbR 2008/09 Nr. 19 vom 16. Juni 2016 - OW Obergericht (2016)
AbR 2008/09 Nr. 19, S. 117: Art. 6 Ziff. 3 lit. d EMRK; Art. 32 Abs. 2 BV; Art. 3, Art. 37 Abs. 2, Art. 116a und Art. 116b StPO; Art. 146 Abs. 2, Art. 147 Abs. 1 und Art. 341 Abs. 2 CH-StPO Das Gericht kann Konfrontationseinvernahmen mit B